A delay tolerant platform for voice message delivery - Chrysostomou, Chrysostomos; Lambrinos, Lambros; Djouvas, Constantinos (My University, 2011)
A voice conversation is predominantly known as a synchronous, delay intolerant form of communication. To complement voice conversations, voice messaging is a form of asynchronous communication used when the called party is unavailable; a delay in message delivery is naturally expected and tolerated. To this extent, a Delay Tolerant Network can be utilized as the underlying data transport mechanism for the delivery of voice messages and in this paper we describe an architecture that combines this technology with the functionality of Voice-over-IP based systems. Our target application concerns the delivery of voice messages that originate from IP-based systems and are destined either for users of other IP-based systems or the Public Switched Telephone Network
Keywords: Communication; Internet telephony; Multimedia systems; Telephone systems